Dirty Hands: The Phenomenology of Acting As an Authorized Agent. - Thalos, Mariam (Monist, 2018)
Traditional articulations of the conception of dirty hands, as the doing of wrong in order to do right, invite construals of the issues raised thereby as mired in conceptual confusions and inconsistencies, and moreover as generating unproductive discussions of the scope of the proposed notion itself. The status of the concept of dirty hands is thus precarious, in spite of its provenance in the work of political thinkers such as Machiavelli. This essay articulates one nonparadoxical conception of dirty hands, as the uncomfortable phenomenology of agents authorized to act on behalf of others, when they are called upon to do things that, while morally correct (or at least putatively so), are also personally or morally distasteful. The key point is that the dirt of action remains on these agents' hands, even if moral responsibility for the relevant actions (when the agents are indeed legitimately authorized to perform them) should be conceived as falling on the persons in whose name they take the said action. This articulation opens up for investigation questions about the phenomenology of authorized agency, as well as the moral labor involved in leadership and in other contexts of authorized distasteful action. These are questions of social ontology. Here there is important philosophical work that remains to be done.